2016
DOI: 10.1536/ihj.15-346
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Biomarkers and Atherosclerosis

Abstract: SummaryAtherosclerosis has been regarded as a form of chronic vascular inflammation. Numerous biomarkers associated with inflammation have been identified as novel targets to monitor atherosclerosis and cardiovascular risk. C-reactive protein (CRP) is one of the most actively studied and established inflammatory biomarkers for cardiovascular events. However, CRP response is triggered by many disorders unrelated to cardiovascular disease, which interferes with the clinical application. This review describes est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
95
2
6

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(108 citation statements)
references
References 53 publications
5
95
2
6
Order By: Relevance
“…9,10) However, very few reports have described a link between statins and sPLA2-IIA expression. Menschikowski, et al found that the expression of sPLA2-IIA in human aorta smooth muscle cells (HASMC) can be increased by statins, and this effect is based on both bJak2-, C/EBP-h-and NF-κB-dependent transcriptional regulation and the stabilization of sPLA2-IIA mRNA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,10) However, very few reports have described a link between statins and sPLA2-IIA expression. Menschikowski, et al found that the expression of sPLA2-IIA in human aorta smooth muscle cells (HASMC) can be increased by statins, and this effect is based on both bJak2-, C/EBP-h-and NF-κB-dependent transcriptional regulation and the stabilization of sPLA2-IIA mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…6,7) Indeed, statins can increase the stability of atherosclerotic plaques by increasing the release of vascular endothelial nitric oxide, 8) improving vascular smooth muscle cell adhesion/migration, and promoting a T helper 2 bias and suppressing the secretion of T helper 1 cytokines. 3) Recently, more and more gene products have been shown to be regulated by statins, such as cyclooxygenase2, 9) inducible nitric oxide (NO) synthase, tumor necrosis factor (TNF), and interleukin (IL)-6, 10) which play a role in inflammation and atherosclerosis.…”
mentioning
confidence: 99%
“…1) Given this unfulfilled need for effective treatment, there is augmenting interest in targeting a novel pathway, inflammation, that underlies CAD and its risk factors. [2][3][4] Further, gut microbiota, which contribute to metabolism and immunity, are current topics as diagnostic and therapeutic targets of CAD. 5,6) The role of gut microbiota in common diseases has been explored mainly due to technical advances such as the use of next generation sequencing to profile samples including fecal microbial DNA together with the development of bioinformatics technology.…”
Section: Oronary Artery Disease (Cad) Is a Growing Epidemic Inmentioning
confidence: 99%
“…1,2) It leads to the narrowing of coronary arteries, which is often asymptomatic early in the course of the disease, but progresses with plaque thickening or plaque rupture, ultimately leading to angina and/or myocardial infarction. [3][4][5][6] The consequences of atherosclerosis represent the most important cause of death in the United States, where the prevalence of atherosclerosis is approximately 6.2% in people > 20 years of age.…”
mentioning
confidence: 99%